QUR’AN MEMORIZERS AND INTERNET: STUDY AT MA’HAD KHOIR-UL-KAYYIS AND MA’HAD KUTUBUSSITTAH BABUSSALAM IN MAKASSAR - Darman Fauzan Dhahir (Journal of Information Technology and Its Utilization, 2018)
The Quran memorization is a highly recommended education in Islam. At the same time the internet has penetrated and become an irremovable part of all fields of human life, including santri life. Some are optimistic, but some are worried about the harm. The present study will discuss on how the internet utilized among Qur’an memorizers, and how it did affect to the achievement of each of them. It is different with the other scholars who have compared different groups of internet user and proposed contradictory conclusions. The surveys confirm that the Quran memorizers who have various techniques of memorizing, all aimed to utilize internet to increase the knowledge, but they are ultimately affected to use for social satisfactions and mere fun. Furthermore, the experiment has resulted that the increasing achievement has been performed during the internet banning, whereas the decrease happened at the access allowance.